Synthesis of ionic liquid-modified BiPO4 microspheres with hierarchical flower-like architectures and enhanced photocatalytic activity. Issue 122 (24th November 2015) - Lv, Hua; Guang, Jing; Liu, Yumin; Tang, Haibo; Zhang, Peng; Lu, Yan; Wang, Jianji
Abstract : Ionic liquid modified onto the surface of BiPO4 can trap photoexcited electrons and enhance the separation of electron–hole pairs. Abstract : In this work, hierarchical flower-like BiPO4 microspheres were successfully synthesized by a microwave-assisted hydrothermal reaction of bismuth nitrate with [C4 mim][PF6 ] (1-butyl-3-methylimidazolium hexafluorophosphate) in water at 160 °C, where the ionic liquid could act as a phosphorus source, surface modified agent and template. The photocatalytic activities of the as-prepared BiPO4 samples were evaluated by decolorization of rhodamine B in aqueous solution under UV light irradiation. It was found that the BiPO4 sample modified with ionic liquid (IL-BiPO4 ) exhibited significantly enhanced photocatalytic activity in comparison with the unmodified one prepared in the absence of [C4 mim][PF6 ]. In addition, the effect of ionic liquid modification on the improved photocatalytic activity was investigated in detail and a possible photocatalytic mechanism was proposed for IL-BiPO4 . It is suggested that the significantly improved photocatalytic activity of IL-BiPO4 could be mainly attributed to trapping of the photoinduced electron at the conduction band of IL-BiPO4 and thus effectively improving the separation efficiency of photoinduced electron–hole pairs due to ionic liquid modification.